2022
DOI: 10.1039/d2ta00654e
|View full text |Cite
|
Sign up to set email alerts
|

First-row transition metal embedded pyrazine-based graphynes as high-performance single atom catalysts for the CO2reduction reaction

Abstract: Single atom catalysts (SACs) have displayed unprecedented activity and selectivity toward electrochemical CO2 reduction reaction (CO2RR). Herein, first-row transition metal embedded pyrazine-based graphynes (TM-pyGYs) were evaluated as potential SACs for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…In this work, the DFT calculation are conducted using Vienna Ab initio Simulation Package 6.1.0 (VASP). [47][48][49] In general, the projector augmented wave (PAW) method is used to deal with electron-ion interactions, [50,51] while the Perdew-Burke Ernzerhof (PBE) exchange correlation functional is used to describe electron interactions in the generalized gradient approximation(GGA). [52] The k-point was set as 3 × 3 × 1 for geometry optimization and 11 × 11 × 1 for electronic structure computation.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, the DFT calculation are conducted using Vienna Ab initio Simulation Package 6.1.0 (VASP). [47][48][49] In general, the projector augmented wave (PAW) method is used to deal with electron-ion interactions, [50,51] while the Perdew-Burke Ernzerhof (PBE) exchange correlation functional is used to describe electron interactions in the generalized gradient approximation(GGA). [52] The k-point was set as 3 × 3 × 1 for geometry optimization and 11 × 11 × 1 for electronic structure computation.…”
Section: Methodsmentioning
confidence: 99%
“…Among various adsorbent materials, metal-organic frameworks (MOFs) have attracted tremendous attention due to their particular properties, including ultrahigh porosity, controllable pore size, and easy functionalization. [8][9][10] Many approaches have been adopted to improve the CO 2 adsorption and separation performances in MOFs. [11][12][13][14][15] Abid et al investigated the CO 2 adsorption behavior in MIL-96(Al) via second metal Ca coordination, and found that the CO 2 adsorption capacity in MIL-96(Al)-Ca1 was enhanced from 8.09 to 10.22 mmol/g at 273 K and 950 kPa.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key challenges in implementing the CCS strategy is the development of adsorbent materials with excellent CO 2 adsorption and separation performances. Among various adsorbent materials, metal‐organic frameworks (MOFs) have attracted tremendous attention due to their particular properties, including ultrahigh porosity, controllable pore size, and easy functionalization [8–10] . Many approaches have been adopted to improve the CO 2 adsorption and separation performances in MOFs [11–15] .…”
Section: Introductionmentioning
confidence: 99%
“…Rapidly increasing CO 2 concentration in the atmosphere due to the burning of fossil fuels has resulted in the greenhouse effect. [ 1–4 ] Carbon capture and storage (CCS) has been proposed to alleviate uncontrolled CO 2 emissions. [ 5–7 ] It is essential to develop suitable adsorbent materials to capture CO 2 .…”
Section: Introductionmentioning
confidence: 99%